Mobile Banking Service Quality on Customer Satisfaction Between Bank Muamalat and Bank Syariah Indonesia - Samsul, Samsul; Fikriyah, Dina; Umar , Hafsah (Adpebi International Journal of Multidisciplinary Sciences, 2022)
The purpose of this study was to determine the effect of mobile banking service quality on customer satisfaction and the differences in service quality on customer satisfaction with the object of research at Bank Muamalat Branch Makassar and Bank Syariah Indonesia (BSI) Branch Pannampu. This study uses an associative-comparative research type with a quantitative approach. The source of data used for this research is primary data. The data collection technique used is a questionnaire, with 100 respondents as the sample. The data analysis technique used in this research is simple linear regression analysis. The results obtained from the current study state that the quality of mobile banking services has a positive and significant effect on customer satisfaction in Bank Muamalat Branch Makassar and Bank Syariah Indonesia (BSI) Branch Makassar Pannampu, each with a sig value of 0.000. This shows that the increasing quality of mobile banking services will also increase customer satisfaction at Bank Muamalat and Bank BSI. There are differences in the quality of m- banking services to customer satisfaction between Bank Muamalat and Bank BSI with a value of 39.66 (39%) and 61.34 (61%). This shows that the quality of mobile banking services at Bank BSI Branch Makassar Pannampu is higher in providing satisfaction to customers than Bank Muamalat Branch Makassar.